Application Of College Task Collection For Informatics And Information System Students - Latius Hermawan; Maria Bellaniar Ismiati (Journal of Computer Science and Engineering (JCSE), 2020)
Abstract: The web is very popular with internet users, because it makes it easy for internet users to search and search for information. Web information system for educational institutions is used as a means to provide, in addition it is used as conducting lecture activities, storing lecture process data and so on. The information that is accessed is very diverse, one of which is for students and lecturers supporting courses is to open an academic portal, collect lecture assignments and create assignments in the form of Information Systems.Existing task collection Web portal, still rarely used by lecturers and students as a media to collect assignments, in fact there are already several features in the existing portal including storing student and lecturer data that teaches, setting the task collection limit, entering the assignment name , etc. Unfortunately the display is not yet user friendly (the display cannot adjust to the device that accesses it automatically) so that if opened on a smartphone, the menu display and writing become smaller, causing menu selection to be more difficult.The results of this study are the construction of a lecture assignment application for students of Informatics and Information Systems that are user friendly. By using this application, students are able to view assignments and collect assignments online while lecturers are able to provide and download assignments online and in real time. Abstrak: Web cepat sekali populer di lingkungan pengguna internet, karena memberikan  kemudahan pada pengguna internet untuk melakukan penelusuran dan pencarian informasi. Web sistem informasi untuk lembaga pendidikan digunakan sebagai sarana untuk memberikan, selain itu digunakan sebagai melakukan kegiatan-kegiatan perkuliahan, penyimpanan data proses perkuliahan dan sebagainya.  Informasi yang diakses sangat beragam, salah satunya bagi para mahasiswa dan dosen pengampu mata kuliah adalah membuka portal akademik, pengumpulan tugas kuliahnya dan pembuatan tugas yang berbentuk Sistem Informasi. Portal Web pengumpulan tugas yang sudah ada, masih jarang digunakan oleh para dosen dan mahasiswa sebagai media mengumpulkan tugas, sebenarnya sudah ada beberapa fitur pada portal yang sudah ada diantaranya penyimpanan data-data mahasiswa dan dosen yang mengajar, pengaturan batas pengumpulan tugas, memasukan nama tugas, dll.  Sayangnya tampilan yang ada belum user friendly (tampilan belum bisa menyesuaikan dengan perangkat yang mengakses secara otomatis) sehingga jika dibuka di smartphone, tampilan menu dan tulisannya menjadi lebih kecil, sehingga menyebabkan pemilihan menu menjadi lebih sulit. Hasil penelitian ini adalah telah dibangunnya aplikasi pengumpulan tugas kuliah bagi mahasiswa Informatika dan Sistem Informasi yang user friendly. Dengan menggunakan aplikasi ini, mahasiswa mampu melihat tugas dan mengumpulkan tugas secara online sedangkan dosen mampu memberikan dan men-download tugas secara online dan real time.